Mechanical behaviors and its main influence parameters of flexible assembly joint of timber column and reinforcement concrete beam. Issue 2 (April 2021) - Wu, Zhongtie; Fan, Pingping
Abstract: Flexible assembly joint is the key problem to coordinate the deformation of hybrid structure. This study aims to investigate the mechanical behaviors and its main influence parameters of flexible assembly joint of timber column and reinforced concrete beam. Finite element models were established and analyzed. The mechanical behaviors of the flexible assembly joint were discussed including the horizontal bearing capacity, horizontal stiffness and load-displacement hysteretic loops. The influence of the vertical load and rubber performance property on the mechanical behaviors of flexible assembly joint was analyzed. The results indicate that the relationship curve of horizontal load and displacement is the bilinear form before its failure. The vertical load and rubber performance property have great influence on its mechanical behaviors including the horizontal bearing capacity, horizontal stiffness and load-displacement hysteretic loops, which are regarded as important indexes to do the performance design.